The Perception of Stress among the Final Year Students in Prosthodontics - Maskey, Brijesh; Shrestha, K.; Mathema, S RB (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: Prosthodontics is a challenging discipline for dental students. This study aims to identify the sources of stress amongst final year undergraduate dental students in prosthodontics at People’s Dental College and Hospital, Nepal. Identifying these potential sources of stress may provide faculties and administrators an opportunity to delineate areas of concern and approach student effectively. Materials and methods: A modified version of the Dental Environment Stress (DES) questionnaire with 22 items was used to assess levels of stress. Results: The major stressors included worry of not completing quotas with a mean score of 3.63 followed by examinations, shortage of allocated clinical and laboratory time, fear of failing a courser the year, overloaded feeling due to huge syllabus, late ending day, responsibility of getting suitable patients, fear of being unable to catch up if behind and patients being late or not showing for their appointments. Amongst these major stressors, the top two stressors were performance pressure related. Conclusions: Although perceived stress in prosthodontics was relatively less than expected, certain areas were highly stressful for majority of the students. There is a need for adopting new strategies by the university, institute, faculties and students themselves for stress management.